Polemics of the Bill on the Alcoholic Beverages’ Prohibition in Indonesia - Marune, Abraham Ethan Martupa Sahat; Tanadi, Irgo Senjaya (Interdisciplinary Social Studies, 2021)
Background: The emergence of the Draft Bill on the Prohibition of Alcoholic Beverages, where it regulates the prohibition on producing, trading, consuming, and other matters related to alcoholic drinks. This certainly causes polemic among the people, because there are several aspect of life related to alcoholic drinks. Aim: Therefore, the author did the research regarding to the effectiveness, impact and challenges faced by the government in the enactment of the Draft Bill on Alcoholic Beverages. Method: The research of this paper is carried out with normative juridical method, qualitative types and documentation instrument methods to examine the relationship between two different but related variables. Findings: From the results of the research, it can be concluded that the drafting of the Alcoholic Drinks Bill in terms of its effectiveness will be very difficult to carry out and its impacts include the cultural, economic, security, and tourism sectors. Each of the Draft Law should be considered entirely in the interest of the people and not personal interests. The government must implement the protocol in accordance with the law and the community must also obey and carry out every right and obligation as citizens who are dedicated and virtuous towards the state constitution.